Exploring the potential public health benefits of universal influenza vaccine - Jay V. DePasse; Mary Patricia Nowalk; Kenneth J. Smith; Jonathan M. Raviotta; Eunha Shim; Richard K. Zimmerman; Shawn T. Brown (Taylor & Francis Group, 2019)
Background: Broadly protective, long-lasting universal influenza vaccines are under development in response to low-moderate seasonal vaccine effectiveness, frequent genetic changes in circulating viruses and extended turnaround for vaccine manufacture. Because a long-lasting vaccine might be less effective than a seasonal vaccine that has been matched to current circulating strains, the public health impact of its introduction should be evaluated. Methods: A modified agent-based model (ABM) examined multi-year effects of a universal vaccine among 18 to 49-year-olds, given in Year 1 only. The proportion of vaccinated 18 to 49-year-olds who received universal vaccine was varied from 0% to 100%. Model parameters were drawn from US databases and the medical literature. Outcomes were 4-year cumulative and annual influenza cases as well as annual cases averted/100,000 population for 3 age groups, 0-17 years, 18-49 years and 50+ years. Results: In Year 1 when universal vaccine was given to 50% or 100% of all vaccinated 18 to 49-year-olds, more influenza cases occurred, compared to no universal vaccine, but fewer cases occurred in Years 2-4 as overall protection increased. Cumulative averted cases over 4 years in 18 to 49-year-olds were 892/100,000 and 1,687/100,000 population for the 50% and 100% universal vaccine for 18 to 49-year-olds scenarios, respectively, with additional benefits to children and older adults through indirect effects. Conclusions: In ABM, the universal vaccine with a conservative VE estimate given once to 18 to 49-year-olds reduced influenza cases among all age groups in Years 2-4 following its introduction. Reduced influenza burden may occur sooner if VE of universal vaccines exceeds that assumed in these models.